The Influence of Financial Management Behavior On MSMES Sustainability of Tourist Attraction Services - Eriyanti, Susi; Dai, Ratna Meisa; Fordian, Dian (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2025)
MSMEs play a crucial role in economic growth, particularly in Pangandaran Village as a tourism destination. The business sustainability of MSMEs in tourist attraction services faces challenges from market competition and changes, which are presumed to be influenced by financial management behavior. This study aims to examine and analyze the influence of financial management behavior on business sustainability of MSMEs in tourist attraction services in Pangandaran Village.The research employed a quantitative descriptive-verification approach, with a sample of 106 MSME operators selected through stratified random sampling. Data were analyzed using simple linear regression. The results demonstrate that financial management behavior has a positive and significant effect on business sustainability (R² = 0.686, p < 0.05). The findings reveal that although MSME operators possess good financial management behavior, improvements are still needed in cash flow management practices, particularly in financial record-keeping and separation of business financial accounts. Furthermore, developing competitive advantages such as providing service packages is essential to enhance business sustainability.